Acute effects of high intensity interval training versus moderate intensity continuous training on haemostasis in patients with coronary artery disease - Daniel Košuta; Marko Novaković; Mojca Božič Mijovski; Borut Jug (Scientific Reports, 2024)
Abstract Exercise training is associated with an acute net increase in coagulation, which may increase the risk of atherothrombosis in coronary artery disease (CAD) patients. We sought to compare the acute haemostatic effects of a bout of moderate-intensity continuous (MICT) and high-intensity interval training (HIIT) in patients with CAD. Patients after a recent myocardial infarction were randomized into a HIIT or MICT session of exercise training on a stationary bike. Blood was sampled at baseline, after the exercise bout and after a one-hour resting period. We measured overall haemostatic potential (OHP), overall coagulation potential (OCP), fibrinogen, D-dimer and von Willebrand factor (vWF) and calculated overall fibrinolytic potential (OFP). Linear mixed models for repeated measures were constructed to assess the treatment effect. A total of 117 patients were included. OCP, OHP, fibrinogen, D-dimer and vWF significantly increased after exercise and returned to baseline after a one-hour rest, OFP decreased after exercise and returned to baseline levels after a one-hour rest. Linear mixed models showed a significant difference between HIIT and MICT in fibrinogen (p 0.043) and D-dimer (p 0.042). Our study has shown that an exercise bout is associated with a transient procoagulant state in patients with CAD, with similar exercise-induced haemostatic changes for HIIT and MICT.